2015
DOI: 10.1185/03007995.2015.1108910
|View full text |Cite
|
Sign up to set email alerts
|

Reaching more children with vaccines in developing countries: key challenges of innovation and delivery

Abstract: As we reach the deadline for the United Nations fourth Millennium Development Goal to reduce child mortality, many inequalities in vaccine access still exist, particularly for children in developing countries. Here we discuss some of the barriers to vaccine access in these countries, as well as some of the innovative approaches that could address these. Finally, we discuss the need to create a global environment conducive to innovation directed at low-resource settings, aimed to ultimately increase vaccine cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…However, the current finding is lower than the findings in Togo 36.2% [20], Worabe, Ethiopia 39% [21], Dominican republic 42.8% [22], Afghanistan, 31% [23], Nigeria 62.8% [9], Angola, 37% [24]. This variation might be due to internal human displacement might increase the risk of defaulting, sociocultural difference, institutional factors like lack of infrastructure and equipments, shortage of supplies, occurrence of natural disaster and endless conflict, time inconvenience, poor recording, registration and defaulter tracing.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the current finding is lower than the findings in Togo 36.2% [20], Worabe, Ethiopia 39% [21], Dominican republic 42.8% [22], Afghanistan, 31% [23], Nigeria 62.8% [9], Angola, 37% [24]. This variation might be due to internal human displacement might increase the risk of defaulting, sociocultural difference, institutional factors like lack of infrastructure and equipments, shortage of supplies, occurrence of natural disaster and endless conflict, time inconvenience, poor recording, registration and defaulter tracing.…”
Section: Discussioncontrasting
confidence: 89%
“…Kaufmann et al (2011) identified a few key reasons for poor performance of VSC in developing countries. Popova and Ibarra de Palacios (2016) discussed some of the barriers to vaccine access in Prioritizing the vaccine supply chain issues developing countries. Riewpaiboon et al (2015) studied the economic analysis of conventional vaccine and logistics systems to the vendor managed inventory in Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Policies must address the need for transportation, storage, and the secure supervision of vaccines to safeguard vaccine administration. 63 Laws can provide requirements around licensure, supply, and production of vaccines to ensure the safety of these vaccines. 64 Licensing regulations assure that each individual in the supply chain is trained on proper vaccine handling and storage.…”
Section: B Supply Chainmentioning
confidence: 99%